Cancer Management: What a Daunting Experience - Leonard, Regina (Operating Room Nurses Association of Canada Journal, 2001)
I work in a health care institution as an operating room nurse and deal with patients every day. I assist them from admission to the suite, to trans- port to the operating room and through their anaesthesia, surgery and discharge to Post Anaesthetic Recovery Room. Often, I felt that my presence and skill had assured, calmed and provided the best care to my patients. Having personally been through the health care system for the past six months, I now have a new appreciation for the patient. I appreciate having had skilled and caring healthcare professionals during my treatments, but I also felt that I was somewhat ownerless in the overall care plan. The past months have been an emotional and physical roller coaster ride. Nothing in my learning or professional experience had prepared me for breast cancer management.